The Influence of Brand Awareness and Engagement in Increasing MSME Consumer Loyalty Through TikTok Social Media in Malang City - Putra Ramadhani Nurwijayanto; Dyah Setyawati; Restu Rahayu Bara; Via Amelia Putri; Elivia Destiana (Business Management Research, 2025)
This study investigates the influence of brand awareness and brand engagement on increasing MSME consumer loyalty through TikTok social media in Malang City. In the digital era, brand awareness and brand engagement on social media, particularly TikTok, are crucial for the success of MSMEs. Consumer loyalty is a vital aspect of marketing strategy, significantly influenced by these factors. The research employed a multiple linear regression method to analyze the relationship between brand awareness (X1), brand engagement (X2), and consumer loyalty (Y). Data was collected from 100 respondents via online questionnaires distributed through Google Forms and analyzed using SPSS. The findings indicate a significant positive effect of brand awareness and brand engagement through social media on consumer loyalty towards MSMEs in Malang City. Based on these results, it is recommended that MSMEs continuously develop engaging and authentic content on TikTok, leveraging its creative features. Additionally, collaboration with local influencers is proposed as an effective strategy to enhance brand awareness, brand engagement, and ultimately, consumer loyalty to MSMEs' products or services.